Adapting the Goal Attainment Approach for Major Depressive Disorder - Maggie McCue; Sagar V. Parikh; Lisa Mucha; Sara Sarkey; Charlie Cao; Anna Eramo; Mark Opler; Briana Webber-Lind; Clément François (Neurology and Therapy, 2019)
Abstract The need for patient-centered care has become a focal point of healthcare improvement initiatives. Shared decision making—in which patients and clinicians communicate about various treatment options and goals and patient input is considered when making treatment decisions—has been associated with improved health and quality of life. A method of treatment evaluation allowing incorporation of patient-specific goals and perspectives is of increasing interest to healthcare providers, payers, and patients. An approach that allows incorporation of shared goal setting is possible via use of an instrument called the Goal Attainment Scale (GAS). This scale provides the structure for measuring progress toward treatment goals set through patient–clinician collaboration. The goal attainment approach has been used as a primary outcomes measure in numerous studies but not in major depressive disorder (MDD). As MDD is a complex, multidimensional disorder affecting each patient differently, the use of GAS methodology is a relevant framework for setting personalized meaningful treatment goals. Initial research into the feasibility of using the GAS in MDD (GAS-D) to measure patient-centric outcomes that may be neglected when more traditional scales are used has been encouraging. The objective of this Commentary is to provide background and rationale for implementation of the GAS-D in clinical practice. Funding Takeda Pharmaceutical Company, Ltd., and Lundbeck LLC.